Neurologic Emergencies Require Rapid Plan of Action - Kuznar, Wayne (MD Conference Express, 2015)
Serious brain- and life-threatening conditions require a high level of clinical discernment, and rapid and effective diagnostic and therapeutic action plans are needed to prevent neurologic injury, suffering, or death. Four categories that clinicians may encounter are acute cerebrovascular emergencies, pediatric neurologic emergencies, neuromuscular emergencies, and the management of seizures in the emergency department or intensive care unit setting.